Matija Murko in dunajska komparativistika - Kramberger, Petra (Primerjalna književnost, 2025)
Matija Murko was one of the most prominent Slavists of his time, yet Germanic philology also played a crucial role in his academic development—an aspect often overlooked in previous research. This article, based on archival materials, matriculation records, and correspondence, examines Murko’s studies and the influence of his professors, particularly Richard Heinzl and Erich Schmidt, on his academic career. His education at the University of Vienna was deeply intertwined with both Slavic and Germanic philology, a dynamic that also shaped his later research. The article illustrates how Murko developed as a scholar who did not confine himself to the study of Slavic literatures but actively engaged with the broader cultural and literary interconnections between the Germanic and Slavic worlds. His interdisciplinary orientation, already evident during his studies, enabled him to attain a comprehensive understanding of literary processes in Central Europe. This article thus highlights the significance of Murko’s Germanic education and underscores the need for a broader perspective on his scholarly work beyond Slavic studies.
Keywords: comparative literature; dunajska univerza; Germanic philology; germanistika; Heinzel, Richard; interdisciplinarity; interdisciplinarnost; literary influences; Murko, Matija; Primerjalna književnost; Schmidt, Erich; Slovenian literary historians; slovenski literarni zgodovinarji; University of Vienna; Vplivi (literarni, umetnostni itd.)